Cochlear patency following translabyrinthine vestibular schwannoma resection: implications for hearing rehabilitation. Issue 7 (3rd July 2019) - Carswell, V; Crowther, J A; Locke, R; Taylor, W; Kontorinis, G
Abstract: Objective: To examine when cochlear fibrosis occurs following a translabyrinthine approach for vestibular schwannoma resection, and to determine the safest time window for potential cochlear implantation in cases with a preserved cochlear nerve. Methods: This study retrospectively reviewed the post-operative magnetic resonance imaging scans of patients undergoing a translabyrinthine approach for vestibular schwannoma resection, assessing the fluid signal within the cochlea. Cochleae were graded based on the Isaacson et al . system (from grade 0 – no obstruction, to grade 4 – complete obliteration). Results: Thirty-nine patients fulfilled the inclusion criteria. The cochleae showed no evidence of obliteration in: 75 per cent of patients at six months, 38.5 per cent at one year and 27 per cent beyond one year. Most changes happened between 6 and 12 months after vestibular schwannoma resection, with cases of an unobstructed cochlear decreasing dramatically, from 75 per cent to 38.5 per cent, within this time. Conclusion: The progress of cochlear obliteration that occurred between 6 and 12 months following vestibular schwannoma resection indicates that the first 6 months provides a safer time window for cochlear patency.